Answer:
For the perfect square trinomial (quadratic) i.e.
, the constant term (last term) is positive.
Step-by-step explanation:
"Perfect square trinomials" are termed as the quadratics that are the outcomes of squaring binomials.
For example:
![\left(x\:+\:3\right)^2](https://tex.z-dn.net/?f=%5Cleft%28x%5C%3A%2B%5C%3A3%5Cright%29%5E2)
![\mathrm{Apply\:Perfect\:Square\:Formula}:\quad \left(a+b\right)^2=a^2+2ab+b^2](https://tex.z-dn.net/?f=%5Cmathrm%7BApply%5C%3APerfect%5C%3ASquare%5C%3AFormula%7D%3A%5Cquad%20%5Cleft%28a%2Bb%5Cright%29%5E2%3Da%5E2%2B2ab%2Bb%5E2)
![a=x,\:\:b=3](https://tex.z-dn.net/?f=a%3Dx%2C%5C%3A%5C%3Ab%3D3)
![=x^2+2x\cdot \:3+3^2](https://tex.z-dn.net/?f=%3Dx%5E2%2B2x%5Ccdot%20%5C%3A3%2B3%5E2)
![=x^2+6x+9](https://tex.z-dn.net/?f=%3Dx%5E2%2B6x%2B9)
Therefore, for the perfect square trinomial (quadratic) i.e.
, the constant term (last term) is positive.
Answer:
So the vaule of y is 7, 10 & 13
Step-by-step explanation:
Given that y = 3x+1 . So we can just substitute x-value into the equation :
Let x=2,
y = 3(2)+1
= 7
Let x=3,
y = 3(3)+1
= 10
Let x=4,
y = 3(4)+1
= 13
The answer is $4.86
12.96 divided by 8 equals 1.62
1.62 •3= $4.86
Answer:
tohw9
ufpa
Step-by-step explanation:
jfapn
abjllj shllhphkvq gohahogsv 79qy75j
Answer:
I'm only here because I'm dumb and I use brainly